Does ibuprofen, prednisolone, or amoxicillin reduce post-tonsillectomy pain in children? A prospective randomized controlled trial. (September 2021) - de Azevedo, Carolina B.; Valera, Fabiana C.P.; Carenzi, Lucas R.; Küpper, Daniel S.; Caetano, João Vitor B.; Queiroz, Danielle L.C.; Anselmo-Lima, Wilma T.; Tamashiro, Edwin
Abstract: Objective: To evaluate whether the use of anti-inflammatory or antibiotic in the postoperative period modifies pain in children undergoing tonsillectomy. Methods: 225 children who underwent cold knife tonsillectomy ± adenoidectomy were randomized into five groups, receiving #1 metamizole/acetaminophen, #2 amoxicillin, #3 ibuprofen, #4 prednisolone, or #5 amoxicillin plus prednisolone. All groups received oral analgesics (metamizole/acetaminophen) to use as needed. Pain was monitored during the 7 days following surgery using the Parents' Postoperative Pain Measurement (PPPM) and the Faces Pain Scale - Revised (FPS-R). Pain was also indirectly evaluated by the dose of analgesics administered on each day and by the time needed to return to a solid diet. Results: After losses (24%), 170 individuals were submitted for analysis. Multiple comparisons demonstrated that the evolution of pain between the different groups, as matched day-per-day, was not significantly different by either PPPM or FPS-R (p > 0.05). The instances of analgesic intake were also similar in all the groups (p > 0.05), as was the return to solid food ingestion (p = 0.41). All groups presented a similar standard of clinical improvement at intervals of 2 days (p < 0.01). Independent of postoperative pain management, patients developed significant pain up to the day 4 following surgery. Conclusion: The addition of amoxicillin, ibuprofen, prednisolone, or amoxicillin and prednisolone does not modify postoperative pain in children undergoing cold-knife tonsillectomy. Special pain control should be performed on the first 4 days following tonsillectomy in children. Highlights: The addition of antibiotics, NSAID, or steroids did not modify post-tonsillectomy pain in children. Pain control should be optimized in the first 4 days following surgery. Most children return to normal activity with low pain scores by day 7 following surgery.